A perspective on diverse adsorbent materials to recover precious palladium and the way forward. Issue 82 (9th November 2017) - Sharma, Shivani; Krishna Kumar, A. Santhana; Rajesh, N.
Abstract : A perspective on diverse adsorbent materials for the recovery of palladium. Abstract : The removal and recovery of precious noble metals is noteworthy in a variety of applications. The need to recover these precious metals is associated with their high cost and other environmental impacts. The Nobel Prize conferred to Suzuki, Heck and Negishi in 2010 has underlined the remarkable significance of palladium as a catalyst in several important transformations. Palladium is one such platinum group noble metal that finds diverse applications in the automobile industry, electronics, jewelry, pharmaceutics, catalysis, etc. Therefore, the recovery of palladium has acquired importance. Methods such as liquid–liquid extraction and adsorption using biopolymers, polymeric resins, carbonaceous materials and silica based materials are discussed based on their removal efficiency, adsorption capacities, regeneration and other parameters. The review looks at a perspective based on the applicability of certain important adsorbents employed in recent years pertaining to the removal of palladium from aqueous solution, spent catalysts and industrial wastes.